The Effect of Pimecrolimus Cream 1% Compared with Triamcinolone Acetonide Paste in Treatment of Atrophic-Erosive Oral Lichen Planus - Atessa Pakfetrat; Zahra Delavarian; Farnaz Falaki; Mahboubeh Khorashadizadeh; Mina Saba (Iranian Journal of Otorhinolaryngology, 2015)
Introduction: Oral lichen planus (OLP) is a common chronic mucocutaneous disease. Patients with atrophic and erosive types of OLP often have symptoms of soreness, and require proper treatment. The main treatment for OLP has been the administration of topical or systemic corticosteroids. The objective of this study was to compare the efficacy of adcortyl cream (triamcinolone acetonide in orabase) with topical pimecrolimus cream for the treatment of erosive OLP.   Materials and Methods: Twenty-eight patients with OLP were enrolled in a single blind clinical trial and assigned to either a pimecrolimus 1% cream group or an adcortyl 0.1% cream group. The medication was applied every day for 2 months and patients were assessed every 2 weeks.   Results: The mean lesion size and mean pain and burning sensation scores did not differ between the pimecrolimus and adcortyl cream groups. The pimecrolimus cream was well tolerated. No clinical drug-related adverse events were observed.   Conclusion:  Topical pimecrolimus cream may be recommended as a safe and effective alternative therapy in the treatment of OLP. Pimecrolimus cream is as effective as adcortyl cream in managing the signs and symptoms of OLP.